Analisis Pendugaan Konsumsi Air dan Nilai Ekonomi Air Sungai Parsariran untuk Kebutuhan Sektor Rumah Tangga - Aswin Pratama; Siti Latifah; Yunus Afifuddin (Program studi Kehutanan USU, 2014)
Water is the most essential need for human and people will pay no matter how to get it, so that the water can be said a non economic good. The forest as the main function of the Hydrological cycle which is a unified system that can’t be separated, but the people in Hapesong Baru village still not understand the value of economic benefits available from water in the Parsariran River. This study aimed to determine the economic value of water in quantitative household in subdistrict of Batang Toru and to determine the economic value estimate household water needs from Parsariran River. This study conducted on August 1 to September 7, 2013, using the model cuantitative collecting data through interviews with respondents. The result showed that the value of the benefits of total household water is Rp. 28,482,522,- - in one year, with an average value of benefits domestic water obtained is Rp. 418 860 , - in one year/household. The model estimates the economic value of water equal to the household sector is Y = 19,86 X1-0,0618. The results can be seen that the value of the economic benefits of domestic water has contributed greatly to the needs of the community .Keywords: Water Consumption Prediction, Economic value of water, Parsariran River